THE PROGNOSTIC VALUE OF BASELINE PSA BLOOD IN THE TREATMENT OF PROSTATE CANCER - A. A. Gritskevich; V. L. Medvedev; S. V. Mishugin; N. A. Apolskaya; I. G. Rusakov (Креативная хирургия и онкология, 2017)
The role of the level of prostate specific antigen ( PSA) before initial therapy discusses widely as a prognostic factor in the  treatment of prostate cancer  (PC ). Despite  the  fact that  many of the questions on the diagnostic and prognostic value of PSA unclear, and new markers  of prostate diseases  are being introduced with increasing  frequency , we assume that  the PSA will continue to be one of the main methods of screening and monitoring of patients with prostate cancer, because of its high diagnostic value due to tissue specificity. Using the  initial PSA level and  Gleason  score  improves  the  predictive  value significantly. This article presents the  results  of a retrospective analysis of 307 patients completed the treatment of  PC. The effect of  baseline  PSA level and  Gleason  score  on  the  choice  of treatment , the effectiveness of hormone deprivation and overall survival are evaluated.